2016
DOI: 10.18632/oncotarget.13012
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA PVT1 promotes osteosarcoma development by acting as a molecular sponge to regulate miR-195

Abstract: A growing body of evidence has indicated that long non-coding RNAs (lncRNAs) serve as competing endogenous RNAs (ceRNAs) during oncogenesis. In this study, the qRT-PCR results indicated that the lncRNA PVT1 is overexpressed in osteosarcoma and decreased the survival rate of osteosarcoma patients. MTT and clonal colony formation assays were used to detect the effect of PVT1 on proliferation, and flow cytometry was performed to assess apoptosis and the cell cycle. A Transwell assay was used to analyze migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 49 publications
2
111
0
Order By: Relevance
“…Also, tumor xenografts experiments suggested that PVT1 knockdown sensitized NSCLC cells to radiotherapy in vivo , which was significantly relieved by miR-195 inhibitor. In line with our study, PVT1 was demonstrated to act as a molecular sponge of miR-195 to promote osteosarcoma development [36]. …”
Section: Discussionsupporting
confidence: 86%
“…Also, tumor xenografts experiments suggested that PVT1 knockdown sensitized NSCLC cells to radiotherapy in vivo , which was significantly relieved by miR-195 inhibitor. In line with our study, PVT1 was demonstrated to act as a molecular sponge of miR-195 to promote osteosarcoma development [36]. …”
Section: Discussionsupporting
confidence: 86%
“…Plasmacytoma variant translocation 1 (PVT1) has been a rising star among lncRNAs, it was transcribed by the human PVT1 gene located in chromosomal 8q24.21[14, 15]. LncRNA PVT1 was reported to play an important role in various cancers [16-18] and function as an oncogene in the development of tumors through promoting cell proliferation, inhibiting cell apoptosis and enhancing cell migration [16-19]. …”
Section: Introductionmentioning
confidence: 99%
“…Of these, 129 duplicated articles were excluded; through title and abstract review, studies describing unrelated topics (n = 80) which refers to those studies that were not research articles or those studies unrelated to osteosarcoma, lncRNA , or patient prognosis were removed; after reading the remaining 54 full-text articles, studies lacking relevant data (n = 32), studies presented in language other than English (n = 1), fulltext unavailable studies (n = 1), and the studies of which included patients were reported in previous studies (n = 1) were excluded. Eventually, 19 studies (containing 1298 patients) met the inclusion criteria and were evaluated in this analysis [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The screening process and results was shown in Figure 1.…”
Section: Included Studies and Characteristicsmentioning
confidence: 99%